How to disappear completely and never be found - Nickerson, Sara (HarperCollins, 2002)
With a swimming medal, the key to a mansion, and a comic book about a half-man/half-rat as her only clues, a twelve-year-old girl seeks the true story of her father's mysterious death four years earlier near an island in the Pacific Northwest.